ANALISIS SIFAT FISIK DAN DAYA DUKUNG TANAH (Studi Kasus: Jl. Lolong Karan, Sungai Sapih, Kec. Kuranji, kota Padang) - Firnandi Firnandi; Fithriyah Patriotika (Department of Civil Engineering, Faculty of Engineering, Universitas Negeri Padang, 2026)
The study is motivated by the occurance of pavement damage in the form of surface deformation, which is presumed to be caused by thre low bearing capacity of the subgrade. the study aims to analyze the physical properties and bearing capacity of soil on jalan Lolong Karan, Sungai Sapih, Kecamatan Kuranji, Kota Padang. The research methods include laboratory testing of soil physical properties, such as water content, specify gravity, Atterberg limits, sieve analysis, and hydrometer analysis, as well as field testing using the Dynamic Cone Penetrometer (DCP) to obtain the California Bearing Ratio (CBR) value. The results show that the soil at the study location is predominantly sandy soil containing silt, with characteristics that influence the soil bearing capacity. THE CBR values obtained from DCP testing are mostly below the minimum standard, indicating that the subgrade as low bearing capacity and is less stable in supporting traffic loads. The main factors influencing this condition are high water content and the surrounding environment, which stabilization are required to increase the soil bearing capacity